Total Synthesis of Mavacuran Alkaloids via Bioinspired and Non-Bioinspired Strategies - Kouklovsky, Cyrille; Poupon, Erwan; Evanno, Laurent; Vincent, Guillaume (Synlett, 2023)
In this account, we report our endeavors towards the total synthesis of the mavacuran alkaloids and some of their highly natural complex bis-indoles. Our studies started with the hemisynthesis of voacalgine A and bipleiophylline, made an excursion to a related family of monoterpene indole alkaloids (total synthesis of 17-nor-excelsinidine) and ended with the total syntheses of several mavacuran alkaloids (16-epi-pleiocarpamine, 16-hydroxymethylpleiocarpamine, taberdivarine H, normavacurine, C-mavacurine, C-profluorocurine, and C-fluorocurine) via a combination of bioinspired and non-bioinspired synthetic routes.1 Introduction2 Bioinspired Hemisynthesis of Voacalgine A and Bipleiophylline3 Total Synthesis of the Mavacuran Alkaloids4 Bioinspired Oxidative Cyclization of a Geissoschizine Ammonium Derivative to Form the N1–C16 Bond and the E Ring5 Non-Bioinspired Michael Addition to Form the C15–C20 Bond and the E Ring6 Conclusion7 Epilogue
Keywords: monoterpene indole alkaloids; bipleiophylline; pleiocarpamine; C-mavacurine; taberdivarine H; C-fluorocurine; biomimetic; oxidative coupling